The Relationship of Transformational Leadership Towards Employees’ Innovation with Mediating Effect of Employees’ Empowerment in UAE Manufacturing Companies - Ahmad, Md Fauzi; Jumaa Alhosani, Jumaa Mohammed; Mohd Nawi, Mohd Nasrun (ExcelingTech, 2019)
– This study aim is to investigate empirically relationship of transformational leadership on employees’ innovation with the mediating effects of employees’ empowerment in this relationship. In past decades, employees’ innovation have become an progressively well-liked way of systematising and organising work. This style makes new tests for leaders, as they are anticipated to encourage individual employees and to improve their performance through innovation consecutively. Conceptual framework for this study, suggests an understanding idea championing and idea implementation which would influence innovative performance of individual employees. The conceptual framework includes employees’ empowerment as mediating variable in the relationship of transformational leadership on employees’ innovation. The study also validates the proposed conceptual framework using a confirmatory factor analysis technique, namely, structural equations modeling, with the data collected from 597 respondents from four e-government organizations in the UAE. The findings suggest that transformational leadership has significant positive impact on employees’ innovation. Moreover, employees’ empowerment have partial mediation effect in the relationship between transformational leadership and employees’ innovation.This study contributes to the research that identifies employees’ innovation influenced by transformational leadership that can affect employee success and performance, particularly in the context of UAE-based e-government organizations.